The relationship between vertebrobasilar artery calcification and intracranial atherosclerosis-related occlusion in thrombectomy - Han, Nannan; Zhang, Gejuan; Yang, Shiyao; Ma, Haojun; Ge, Hanming; Zhang, Xiao; Li, Shilin; Wang, Yanfei; Fan, Xiaonan; Yin, Yanling; Gao, Yanjun; Shi, Wenzhen; et al. (Frontiers in Neurology, 2022)
Background and Purpose： Distinguishing between intracranial atherosclerosis-related occlusion (ICAS-O) and non-ICAS-O can benefit strategies of identifying the need for surgical plans prior to thrombectomy. We investigated the association between vertebrobasilar artery calcification (VBAC) and ICAS-O in acute ischemic stroke patients undergoing thrombectomy. Methods： Patients were recruited from a prospective single-center registration study who had undergone thrombectomy between October 2017 and October 2021. The enrolled patients were divided into ICAS-O and non-ICAS-O, as determined by the intraarterial therapy process. The occurrences of VBAC were recorded on intracranial non-contrast computed tomography (NCCT) scans before thrombectomy. The association between VBAC and ICAS-O was assessed using binary logistic regression. Results： A total of 2732 patients who had undergone digital subtraction angiography were reviewed, and 314 thrombectomy patients (mean age: 65.4 years, 36.6% female) with NCCT were enrolled in this study. VBAC was detected before thrombectomy in 113 (36%) out of 314 patients. Age, hypertension, and diabetes were associated with VBAC, and a higher frequency of VBAC was identified in patients presenting posterior circulation. ICAS-O accounts for 43% (135/314) in eligible patients. From multivariable analyses, VBAC was identified as an independent predictor of ICAS-O (adjusted odds ratio, 6.16 [95% CI, 2.673-14.217], P<0.001). Meanwhile, the (VBAC[+] atrial fibrillation[-]) group displayed higher rates of ICAS-O than the (VBAC[-] atrial fibrillation [-]) group (P<0.001). Conclusions: We demonstrated that VBAC is an independent risk factor for ICAS-O in patients who underwent thrombectomy. Patients free of atrial fibrillation with VBAC have more trend to be ICAS-O.